Ex vivo pharmacokinetic and pharmacodynamic analysis of valnemulin against Mycoplasma gallisepticum S6 in Mycoplasma gallisepticum and Escherichia coli co-infected chickens. Issue 1 (April 2015) - Xiao, Xia; Sun, Jian; Chen, Yi; Zou, Mengting; Zhao, Dong-Hao; Liu, Ya-Hong
Highlights: Matrix effects were evaluated in an MIC determination of Mycoplasma gallisepticum . Ex vivo PK/PD modeling of valnemulin administered to infected chickens was performed. A dosage of 12.4 mg/kg/day valnemulin was calculated for mycoplasmacidal activity. Abstract: Pharmacokinetic and pharmacodynamic (PK/PD) indices against Mycoplasma gallisepticum (MG) S6 were investigated in an ex vivo PK/PD model following oral administration of valnemulin to chickens co-infected with M. gallisepticum and Escherichia coli . The minimum inhibitory concentrations (MICs) for valnemulin against MG S6 in artificial medium and chicken serum were determined. In vitro time–killing curves were established according to a series of multiples of the MIC value in an artificial medium, and ex vivo time–killing curves were established in serum samples obtained from infected chickens at different time points after oral administration with an initial titer of 1 × 10 6 color change units (CCU)/mL MG S6. The sigmoid Emax model was used to provide 24 h area under concentration–time curve/minimum inhibitory concentration ratios (AUC0–24h /MIC) for mycoplasmastasis, mycoplasmacidal activity and mycoplasmal elimination, respectively. The inoculum size and micro or macro methods exhibited little effect on MIC determination of MG, whereas matrix had a large effect. The rapid killing activity observed in in vitro time–killing curves seems to indicate that valnemulin was mycoplasmacidal and concentration dependent against MG. The AUC0–24h /MIC ratio for mycoplasmacidal activity and mycoplasmal elimination was 1321 h and 1960 h, respectively. A dosage regimen of 12.4 mg/kg/day and 18.3 mg/kg/day valnemulin was calculated for mycoplasmacidal activity and mycoplasmal elimination against MG S6, respectively.